Game level design : game development essentials. - Castillo, Travis, ....-; Novak, Jeannie, 1966- (New York : Delmar Cengage Learning, 2008)
Learn how to design game levels for the next generation of game engines with Game Development Essentials: Game Level Design. This book takes the reader on a creative journey that starts at a conceptual beginning and arrives at a polished end. Through this journey, you will learn the process of designing compelling worlds that immerse the player in interactive environments created from your imagination. Visceral worlds that tell a story through their aesthetics are combined with a refined design that allows the player to flow through a level. Learn to draw inspiration from the world around you and translate your ideas into playable game worlds!